Patient perceptions of oral health care following stroke: a qualitative study - Shilpi Ajwani; Caleb Ferguson; Ariana C. Kong; Amy R. Villarosa; Ajesh George (BMC, 2021)
Abstract Background Stroke is a serious cerebrovascular disease and is one of the world's leading causes of disability. Maintaining good oral health is a challenge among those hospitalised after stroke. A multidisciplinary approach to oral care involving non-dental professionals can be beneficial in improving oral health outcomes for patients. The aim of this study was to understand the perceptions of stroke survivors regarding oral healthcare across acute and rehabilitation settings. Methods A descriptive qualitative approach was used. Face-to-face semi-structured interviews were conducted. A framework analysis was employed to analyse the data. Patients who had recently experienced a stroke were purposively recruited across both acute and rehabilitation settings, at two metropolitan hospitals in Sydney, Australia. In total, 11 patients were interviewed. Results Although participants recognised the importance of oral health, few understood the link between oral and general health. Regular oral hygiene practices varied since having stroke, with a few receiving oral care assistance from nurses. Time, cost and lack of information were some barriers to accessing dental services, while supportive measures such as coordination of oral care, financial subsidy and nurse assistance were strategies proposed to support oral care practices amongst stroke survivors. Conclusions There is scope to improve current models of oral care in stroke. While stroke survivors understand the importance of oral care, an integrated oral health model with a multidisciplinary approach could improve health outcomes.